Potential Trace Metal–Organic Complexation in the Atmosphere - Hiroshi Okochi; Peter Brimblecombe (The Scientific World Journal)
It is possible that metal–organic complexation enhances the uptake of gaseous organic compounds and the solubility of metals in aerosols and atmospheric water. We investigated potential atmospheric organic ligands and the enhanced uptake of hydroxy-, oxo-, and dicarboxylic acids as well as dicarbonyls into atmospheric aqueous aerosol. We examined complexation with transition metals (iron, manganese, nickel, copper, zinc) and lead on the basis of available references and our experimental data. Humic-like substances are most likely ligands in the atmosphere, although this is a poorly characterized material. A number of polycarboxylic acids and hydroxy forms (e.g., citric and tartronic acids) effectively complex metals such as copper in atmospheric aerosols. The simple equilibrium model calculations show that the effect of the complexation on the gas–aqueous phase partition of gaseous atmospheric ligands is quite small for the ligands with the high physical Henry’s law constants, e.g., dicarboxylic acids represented by oxalic acid, even if they have high affinity with metal ions. The lower Henry’s law constants of the α-dicarbonyls, such as glyoxal and methylglyoxal, mean that the complexation could lead to profound increases in their partition into the aqueous phase. Despite quantum mechanical arguments for copper–glyoxal complexes, experiments showed no evidence of complexation between either hydrated or unhydrated α-dicarbonyls and the cupric ion. By contrast the β-dicarbonyl, malondialdehyde, has properties that would allow it to partition into atmospheric water via the complexation with metal ions under some conditions.